2020
DOI: 10.18632/aging.103389
|View full text |Cite
|
Sign up to set email alerts
|

circKIF4A sponges miR-127 to promote ovarian cancer progression

Abstract: Ovarian cancer is a major gynecologic cancer and common cause of gynecologic cancer death worldwide. However, the molecular mechanisms of ovarian cancer progression are still unclear. circular RNAs (circRNAs) are recently reported to be involved in cancer progression regulation but the potential functions of circRNAs in ovarian cancer remains unknown. In this study, we explored the expression of circKIF4A in ovarian cancer tissues. Then, a series of experiments were conducted to investigate how circKIF4A funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…circKIF4A is highly expressed in ovarian carcinoma and can promote cancer cell multiplication and metastasis [ 29 ]. It is also up-regulated in bladder cancer and can promote carcinoma cell metastasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…circKIF4A is highly expressed in ovarian carcinoma and can promote cancer cell multiplication and metastasis [ 29 ]. It is also up-regulated in bladder cancer and can promote carcinoma cell metastasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are highly expressed in cells and tissues, and are potential miRNA sponges for regulating the expressions of various key genes closely relatively to malignant tumor [22]. circKIF4A is signi cant in malignant progression of a variety of tumors [8][9][10][11][12][13]. We tested circKIF4A levels in OS cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes from a larger cohort showed that circ-0001068/miR-28-5p in T cells induced PD1 expression, and this caused in T-cell exhaustion [91]. Circ-KIF4A and circ-0025033 promote OC progression by absorbing miR-127 and miR-184, respectively [92,94]. In 2020, another study was conducted on circ-0025033 that confirmed its role in cell viability, invasion [93].…”
Section: Roles In Clinical Implications Of Ocmentioning
confidence: 95%
“…Numerous studies have shown that circ-0015756, circ-0002711, hsa-circ-0015326, circ-0001068, circ-0025033 and circ-KIF4A are oncogenic circRNAs with diagnostic and prognostic value in OC [88][89][90][91][92][93][94]. Their function occurs through sponge of corresponding miRNAs.…”
Section: Roles In Clinical Implications Of Ocmentioning
confidence: 99%